2010
DOI: 10.1016/j.jhevol.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Bipedal tool use strengthens chimpanzee hand preferences

Abstract: The degree to which non-human primate behavior is lateralized, at either individual or population levels, remains controversial. We investigated the relationship between hand preference and posture during tool use in chimpanzees (Pan troglodytes) during bipedal tool use. We experimentally induced tool use in a supported bipedal posture, an unsupported bipedal posture, and a seated posture. Neither bipedal tool use nor these supported conditions have been previously evaluated in apes. The hypotheses tested were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 73 publications
4
47
0
1
Order By: Relevance
“…Unimanual actions were single-handed lateralized (left, right) actions that were directed toward, and made physical contact with, animate (conspecific, self) or inanimate (objects, ground, enclosure) target objects, while the other hand remained physically inactive. In order to avoid postural confounds, unimanual actions were considered only when both hands were equally available to perform the task (Aruguete et al 1992;Braccini et al 2010;Westergaard et al 1998) (see Table 1). Therefore, in cases where one hand reached toward a target object but the other hand was used for postural support, locomotion or a separate manual activity, the action was excluded from analyses.…”
Section: Coding Categorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unimanual actions were single-handed lateralized (left, right) actions that were directed toward, and made physical contact with, animate (conspecific, self) or inanimate (objects, ground, enclosure) target objects, while the other hand remained physically inactive. In order to avoid postural confounds, unimanual actions were considered only when both hands were equally available to perform the task (Aruguete et al 1992;Braccini et al 2010;Westergaard et al 1998) (see Table 1). Therefore, in cases where one hand reached toward a target object but the other hand was used for postural support, locomotion or a separate manual activity, the action was excluded from analyses.…”
Section: Coding Categorizationmentioning
confidence: 99%
“…Within an evolutionary context, it has been suggested that right-handedness emerged as a result of speech (Annett 2002), gestural language (Corballis 2002;, tool use (Breuer et al 2005;Greenfield 1991), coordinated bimanual actions Wundrum 1986), posture (MacNeilage et al 1987) and bipedalism (Braccini et al 2010;Westergaard et al 1998). To investigate these evolutionary hypotheses, many researchers study the behaviors of our closest living biological relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Human population-level right-handedness has been theorized to have evolutionary links with gesture [9,10], speech [11], tool use [e.g. 12], coordinated bimanual actions [13,14], posture [15] and bipedalism [16,17]. Scientists have been drawn to the unique coupling of manual action and brain organization for skilled communication in the hopes that it may shed light on the origins of human language.…”
mentioning
confidence: 99%
“…The evaluation of the gorillas' hand preference was based on 2 measures. The first measure determined a binomial z-score for each subject, based on the total frequency of right-and left-hand task responses [Braccini et al, 2010]. We classified gorillas with z-scores higher than 1.96 or less than -1.96 as right-or left-handed, respectively (p !…”
Section: Methodsmentioning
confidence: 99%